REDISTRIBUSI KEKUASAAN NEGARA DAN HUBUNGAN ANTAR LEMBAGA NEGARA DI INDONESIA - Rahmat Robuwan (Fakultas Hukum Universitas Bangka Belitung, 2018)
The relationship between state agencies basically can not be separated from the system used by the state government itself. Indonesia as a country that adopts a presidential government certainly has a pattern of distribution of power, although theoretically the presidential government system power state agency separate (separation of power), but the relationship between institutions is not a relative. The mechanism of checks and balances of power destribusi state institutions. Before the amendment, the agency is the State Supreme People's Representative Council (DPR), the President, the Supreme Audit Agency CPC, the Supreme Advisory Council (DPA) and the Supreme Court with the vertical power distribution. Following the amendment to the state institutions teridir of the President, the People's Consultative Assembly (MPR), House of Representatives (DPR), the Regional Representatives Council (DPD), the Supreme Audit Agency (BPK), the Supreme Court (MA), and the Constitutional Court (MK) with distribution horizontal power - functional. The distribution of power still has a problem among others, the discontinuity in the distribution of state agencies ranging from the overlapping powers of the president in participating deliberating the bill with the House, the confusion related to the division between the authority of the Supreme Court and the Constitutional Court in the perspective of the state administration, the inconsistency of the parliamentary system that it wants to apply and the lack of authority DPD in parliament.